Kinetic Modeling of Hyperpolarized (13)C Label Exchange between Pyruvate and Lactate in Tumor Cells - Witney, Timothy H. (American Society for Biochemistry and Molecular Biology, 2011)
Measurements of the kinetics of hyperpolarized (13)C label exchange between [1-(13)C]pyruvate and lactate in suspensions of intact and lysed murine lymphoma cells, and in cells in which lactate dehydrogenase expression had been modulated by inhibition of the PI3K pathway, were used to determine quantitatively the role of enzyme activity and membrane transport in controlling isotope flux. Both steps were shown to share in the control of isotope flux in these cells. The kinetics of label exchange were well described by a kinetic model that employed rate constants for the lactate dehydrogenase reaction that had been determined previously from steady state kinetic studies. The enzyme showed pyruvate inhibition in steady state kinetic measurements, which the kinetic model predicted should also be observed in the isotope exchange measurements. However, no such pyruvate inhibition was observed in either intact cells or cell lysates and this could be explained by the much higher enzyme concentrations present in the isotope exchange experiments. The kinetic analysis presented here shows how lactate dehydrogenase activity can be determined from the isotope exchange measurements. The kinetic model should be useful for modeling the exchange reaction in vivo, particularly as this technique progresses to the clinic.